2005
DOI: 10.1359/jbmr.041109
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Localization and Neutralization of the SDF-1(CXCL12)/CXCR4 Axis Blocks Prostate Cancer Metastasis and Growth in Osseous Sites In Vivo

Abstract: To delineate the role of SDF-1 and CXCR4 in metastatic prostate cancer (CaP), positive correlations were established between SDF-1 levels and tumor metastasis. Neutralization of CXCR4 limited the number and the growth of intraosseous metastasis in vivo. Together, these in vivo metastasis data provide critical support that SDF-1/CXCR4 plays a role in skeletal metastasis.Introduction: Previously we determined that the stromal-derived factor-1 (SDF-1)/CXCR4 chemokine axis is activated in prostate cancer (CaP) met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
273
2
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 353 publications
(291 citation statements)
references
References 44 publications
(100 reference statements)
12
273
2
4
Order By: Relevance
“…To examine the localization of SDF-1 protein expressed during the acute phase of live bone graft healing, immunohistochemical analysis was performed. The expression of SDF-1 protein was observed at the growth plate and the endosteum (results not shown), as previously reported (32). We also detected high expression of SDF-1 protein at the periosteum of the bone graft on day 2 ( Figure 1B, bottom left).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…To examine the localization of SDF-1 protein expressed during the acute phase of live bone graft healing, immunohistochemical analysis was performed. The expression of SDF-1 protein was observed at the growth plate and the endosteum (results not shown), as previously reported (32). We also detected high expression of SDF-1 protein at the periosteum of the bone graft on day 2 ( Figure 1B, bottom left).…”
Section: Resultssupporting
confidence: 89%
“…To answer this, we performed gene expression and immunohistochemical analysis and observed that the periosteum of the long bones indeed expressed SDF1 mRNA, and that the expression of SDF-1 protein was highly increased in the periosteum of the live grafts, while no remarkable increase was observed either in the periosteum of the host bone or in that of the dead grafts ( Figures 1B and C). It was previously reported that SDF-1 is expressed at the endosteum and the growth plate of normal long bones in adults (32), but a recent study showed that SDF-1 is expressed at the periosteum during embryonic endochondral bone development, and that expression is substantially reduced after birth (38). Combined with these reports, our results may lead to an interesting hypothesis that, in endochondral bone repair, progenitor cells in the periosteum regain the embryonic state and recruit MSCs through the up-regulation of SDF-1 expression, which is consistent with a wellaccepted hypothesis that fracture healing recapitulates normal bone growth.…”
Section: Discussionmentioning
confidence: 98%
“…A recent report further supports the role of CXCL12/CXCR4 in prostate cancer bone metastasis using the intratibial model in which inhibition of CXCR4 function reduced bone tumor growth (4). Experimental manipulation of CXCR4 also affects secondary tumor growth in lymph nodes.…”
Section: Discussionmentioning
confidence: 67%
“…Furthermore, binding of CXCL12 to CXCR4 has been shown to play a crucial role in site-specific metastasis to lymph nodes, lung, and bone (1). In prostate cancer, we and others showed CXCL12/CXCR4 signaling in tumor cells when in bone tissue (2)(3)(4). We also showed that CXCL12/CXCR4 interaction leads to mitogen-activated protein kinase and phosphoinositide 3-kinase/Akt -mediated MMP-9 expression, migration, and invasion of prostate cancer cells (2).…”
Section: Introductionmentioning
confidence: 99%
“…SDF-1 levels are highest in the pelvis, tibia, femur, liver, and adrenal/ kidneys compared with the lungs, tongue, and eye. Antibody to CXCR4 significantly reduces skeletal metastases [67]. High-density tissue microarrays constructed from clinical samples obtained from a cohort of over 600 patients demonstrates that CXCR4 protein expression is significantly elevated in localized and metastatic cancers [68].…”
Section: Chemotaxis Towards Bonementioning
confidence: 99%